2012
DOI: 10.1371/journal.pone.0036185
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine Inhibits Histamine H1 Receptor-Induced Ca2+ Signaling in Rat Hypothalamic Cells

Abstract: The hypothalamus in the brain is the main center for appetite control and integrates signals from adipose tissue and the gastrointestinal tract. Antidepressants are known to modulate the activities of hypothalamic neurons and affect food intake, but the cellular and molecular mechanisms by which antidepressants modulate hypothalamic function remain unclear. Here we have investigated how hypothalamic neurons respond to treatment with antidepressants, including desipramine and sibutramine. In primary cultured ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hypothalamic AMPK is also involved in feeding regulation and food intake by regulating the AMPK-ACC-Malonyl-CoA-CPT1 axis (ACC: acetyl-CoA carboxylase; CPT1: carnitine palmitoyltransferase 1) [91][92][93][94]. A study using the CT1-1 cell line reported that the protein level of phosphor-AMPK (pAMPK) is activated by the H 1 R antagonist chlorpheniramine, while it is blocked by histamine [95].…”
Section: The Role Of Hypothalamic H 1 R-ampk Signalling In Sga-inducementioning
confidence: 99%
“…Hypothalamic AMPK is also involved in feeding regulation and food intake by regulating the AMPK-ACC-Malonyl-CoA-CPT1 axis (ACC: acetyl-CoA carboxylase; CPT1: carnitine palmitoyltransferase 1) [91][92][93][94]. A study using the CT1-1 cell line reported that the protein level of phosphor-AMPK (pAMPK) is activated by the H 1 R antagonist chlorpheniramine, while it is blocked by histamine [95].…”
Section: The Role Of Hypothalamic H 1 R-ampk Signalling In Sga-inducementioning
confidence: 99%
“…Recently, a study on the hypothalamic GT1-1 cell line also found similar results; the H1 receptor antagonist, chlorpheniramine, increased the protein level of phosphor-AMPK (pAMPK: activated AMPK), which could be blocked by histamine. [73] A range of evidence has demonstrated that activation of hypothalamic AMPK increases food intake and body weight, while inhibition of hypothalamic AMPK decreases feeding and body…”
Section: The Role Of Histamine and Histamine H1 Receptors In Second-gmentioning
confidence: 99%
“…We observed an increase in the level of phospho AMPK and plasma adiponectin. A study by Kang et al [40] has shown similar results for AMPK and an increase in serum adiponectin with sibutramine administration has been reported [41,42]. No previous studies have reported the effect of sibutramine on CPT-1 activity.…”
Section: Discussionmentioning
confidence: 52%